An Ultralight Capillary-Driven Heat Pipe - Lee, Yong Ju (Langmuir : the ACS journal of surfaces and colloids, 2024)
Capillary-driven heat pipes are an effective thermal solution for compacting electronic cooling systems. We advance such a heat pipe thermal solution with ultralightweighting for mobile applications. In our advancement, the envelope that encapsulates the phase-change process of a working fluid is fabricated via electroless plating being ∼40 μm thick. Furthermore, the wick structure that transports condensate to a heat source via capillarity is also electroless-plated onto the envelope's inner surfaces, creating a 100-μm-thick, microporous layer. This wick structure is sequentially superhydrophilized by blackening that forms a nanotexture on the microporous wick layer. An effective density of our prototype ultralight heat pipes (uHPs), as a measure of lightweighting, indicates, on average, a remarkable 73% weight reduction of commercial counterparts with sintered copper powder wick in similar exterior dimensions (e.g., ∼2.7 g, compared to ∼10.0 g) while providing equivalent heat spreading. Furthermore, the uHP operates at a 25% lower evaporator temperature, due to additional heat rejection to the surroundings through the ultrathin-walled envelope and wick